TI_GERICHTE 11.2019.107 vom 5. Oktober 2020 , Derelizione di una quota di comproprietà coattiva ("dipendente") - TI Tribunale d'appello (2020)
Derelizione di una quota di comproprietà coattiva ("dipendente")